2011
DOI: 10.1007/s10802-011-9495-5
|View full text |Cite
|
Sign up to set email alerts
|

Attention Biases to Threat Link Behavioral Inhibition to Social Withdrawal over Time in Very Young Children

Abstract: Behaviorally inhibited children display a temperamental profile characterized by social withdrawal and anxious behaviors. Previous research, focused largely on adolescents, suggests that attention biases to threat may sustain high levels of behavioral inhibition (BI) over time, helping link early temperament to social outcomes. However, no prior studies examine the association between attention bias and BI before adolescence. The current study examined the interrelations among BI, attention biases to threat, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
260
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(294 citation statements)
references
References 92 publications
26
260
2
1
Order By: Relevance
“…In these younger populations, attentional biases for emotional stimuli are usually not found (Heim-Dreger, Kohlmann, Eschenbeck, & Burkhardt, 2006;Pérez-Edgar et al, 2011;Roy et al, 2008;Susa, Pitică, Benga, & Miclea, 2012;Waters, Kokkoris, Mogg, Bradley, & Pine, 2010;Waters, Mogg, Bradley, & Pine, 2008), although a recent study found avoidance of negative faces and vigilance for positive faces in 8-year-old children (Brown et al, 2013). Brown et al (2013) used a combination of facial expressions as negative stimuli whereas the other studies only used angry expressions, which might explain the different results.…”
Section: Subjectsmentioning
confidence: 95%
“…In these younger populations, attentional biases for emotional stimuli are usually not found (Heim-Dreger, Kohlmann, Eschenbeck, & Burkhardt, 2006;Pérez-Edgar et al, 2011;Roy et al, 2008;Susa, Pitică, Benga, & Miclea, 2012;Waters, Kokkoris, Mogg, Bradley, & Pine, 2010;Waters, Mogg, Bradley, & Pine, 2008), although a recent study found avoidance of negative faces and vigilance for positive faces in 8-year-old children (Brown et al, 2013). Brown et al (2013) used a combination of facial expressions as negative stimuli whereas the other studies only used angry expressions, which might explain the different results.…”
Section: Subjectsmentioning
confidence: 95%
“…Waters and colleagues [13] found that, in children with Generalized Anxiety Disorder, only severe anxiety or the presence of social phobia was linked to attentional bias to threat on a visual probe task using faces. Similarly, Perez-Edgar and colleagues [14] found that behaviorally inhibited preschoolers (vulnerable to social anxiety) showed more stable forms of social withdrawal if they oriented towards threats in a dot-probe task than if they did not. Complicating these diagnostic specificity findings, however, is the high degree of comorbidity found among anxiety disorders in prepubertal children [1].…”
Section: Introductionmentioning
confidence: 91%
“…They are also associated with behavioral outcomes early in development. For example, a recent study demonstrated that attentional biases to threat predicted whether temperamentally inhibited children would demonstrate social withdrawal behaviors at age five [63]. Moreover, recent research has extended ABM training to anxiety reduction in children, as well.…”
Section: Individual Differences In Affect-biased Attentionmentioning
confidence: 99%